Final report on industrial orientation with Turbine Overhaul Services Pte Ltd - Sia, Marcus Wenhui (2015)
This report presents the summary of the author's experience during the 10 week duration as an Industrial Orientation student at Turbine Overhaul Services (TOS) Private Limited, under the Repair Development Engineering / Special Processes (RDE/SP) Department. The author worked together with and supported the engineers of TOS RDE/SP to design and produce laser cladding and welding operations.